Analysis of the Current Maintenance Management Process in School Buildings: Study Area of Primorje-Gorski Kotar County, Republic of Croatia - Tijanić Štrok, Ksenija; Marenjak, Saša; Car-Pušić, Diana (Frontiers in Built Environment, 2022)
Due to their educational purpose, impact on users and quality of education, school buildings are vital institutions in the community, and their adequate maintenance should be mandatory. Studies conducted around the world point to specific inadequacies that occur in the school maintenance segment, however studies that examine the entire maintenance management process in detail are rare. With such studies, it is possible to observe all components of maintenance and its management in the observed buildings, it is possible to get a detailed insight into the present inadequacies and problems, and give the best possible answer to them. Observing the territory of the Republic of Croatia, it was noticed that there are no adequate databases on school building maintenance. Given all the above, this paper aims to establish a methodological framework and analyze the entire maintenance management process in Croatian schools to detect potential inadequacies, reveal problems, and identify areas for action to improve maintenance performance and carry out maintenance more efficiently. The current maintenance management process of elementary school buildings in the Primorje-Gorski Kotar County, Republic of Croatia, was examined based on the developed methodological framework. Data on the management process were collected through a questionnaire survey among school principals. The questionnaire was compiled based on an extensive literature review. Maintenance performance through management functions was investigated, namely: maintenance planning, maintenance organization, maintenance directing, and maintenance controlling. Important management factors within each of the mentioned functions were observed. The data analysis revealed specific inadequacies and problems in the maintenance process, and it was shown that maintenance management is not entirely effective. Recommendations were given to improve the current situation. In this way, it is possible to quickly and easily examine the entire management process and identify measures that need to be introduced in schools to improve their business in the maintenance segment. The developed methodological framework can be applied to schools from other areas as well as to other types of buildings.